2021
DOI: 10.1371/journal.pone.0247960
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of abdominal obesity among the adult population in Woldia town, Northeast Ethiopia, 2020: Community-based cross-sectional study

Abstract: Background The prevalence of abdominal obesity has been dramatically increasing both in developed and developing countries, including Ethiopia. It is an independent risk factor for cardiovascular diseases, type-2 diabetes mellitus, high blood pressure, and cancer. However, there is inadequate data regarding the prevalence and associated factors of abdominal obesity among adult population in Ethiopia. Objective This study aimed to assess the prevalence and associated factors of abdominal obesity among the adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
19
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 43 publications
12
19
3
Order By: Relevance
“…In this study, women had 13 times higher odds of central obesity compared to men. This finding is corroborated by similar studies in different parts of Ethiopia (35)(36)(37)(38)(39). Similarly, studies conducted by Jaacks et al, suggested that in countries with stage 1 obesity transition, the prevalence of obesity is higher among women compared to men (45).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In this study, women had 13 times higher odds of central obesity compared to men. This finding is corroborated by similar studies in different parts of Ethiopia (35)(36)(37)(38)(39). Similarly, studies conducted by Jaacks et al, suggested that in countries with stage 1 obesity transition, the prevalence of obesity is higher among women compared to men (45).…”
Section: Discussionsupporting
confidence: 88%
“…In comparison to men, women had a higher prevalence of central obesity (53.1% vs 15.4%). The figures reported in this study are comparable with studies conducted in Gondar and Dabat towns, Northwest Ethiopia (37.6% & 33.6%) (37,43), but higher than the studies conducted in Nekemte town, West Ethiopia (28.4%) (35), Woldia town, Northeast Ethiopia (15.5%) (36), and Dilla town South Ethiopia (24.4%) (38). The possible variations of the obesity prevalence could be explained by the use of different cutoff values for waist circumferences (36) and the variation of age distributions between the studies participants (35,38).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations